Differences between female and male patients with familial rheumatoid arthritis. Issue 4 (1st April 2001) - Laivoranta-Nyman, S; Luukkainen, R; Hakala, M; Hannonen, P; Möttönen, T; Yli-Kerttula, U; Ilonen, J; Toivanen, A
Abstract : OBJECTIVE: To determine whether there are genetic differences between female and male patients with familial rheumatoid arthritis (RA). METHODS: 45 men and 119 women from 78 families with RA who all had at least one first degree relative with RA were compared. HLA-DRB1 alleles were analysed, including DRB1*04 subtypes and associations of DRB1*04 haplotypes with DQB1*0301 or DQB1*0302 alleles, the age of the patients at disease onset, the presence of rheumatoid factor (RF), joint erosions, and rheumatoid nodules. RESULTS: HLA-DRB1*13 allele (the subtype allele of DR6, reported to be protective against the development of RA) was found in 14/119 (12%) of female but in none of the male patients (p=0.036). The HLA-DR4 allele was found slightly more often in men than women patients with familial RA (31/45 (69%) v 75/119 (63%), NS). Men were also more often RF positive than women (44/45 (98%) v 98/117 (84%); p=0.031). On the other hand, the mean age at onset of RA was significantly lower in the female group (40.4 years) than in men (46.6 years, p=0.0044). CONCLUSION: The results indicate that there is stronger genetic background in familial male than female patients with RA in the genetic susceptibility defined by the studied HLA antigens. However, the earlier age of onset of the disease in female group and the increased proportion of women with RA indicate that there are additional sex related predisposing factors enhanced in familial cases.